2021
DOI: 10.3390/nu13030714
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule Membrane Supplementation in Children: Systematic Review with Meta-Analysis

Abstract: (1) Background: Milk fat globule membrane (MFGM), composing fat droplets responsible for lipid transport in breast milk, has been shown to possess immunological and antimicrobial effects. Standard formulas (SF) are devoid of MFGMs during the production process. The study’s aim was to evaluate the safety and benefits of MFGMs supplementation in children. (2) Methods: We searched four databases for randomized controlled trials evaluating the supplementation of MFGMs in children. Growth parameters were chosen as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
(126 reference statements)
0
16
0
Order By: Relevance
“…The growth outcomes of infants fed formula supplemented with these ingredients are worth evaluating. Some systematic reviews about comparisons between infants fed with standard formula and those fed with milk fat globule membrane-supplemented formulas, palm olein-containing formulas, prebiotic-supplemented formulas, or taurine-containing formulas revealed no differences in anthropometric measurements [ 50 , 51 , 52 , 53 ]. A meta-analysis by Wang et al indicated that nucleotide supplementation could increase the rate of weight gain; however, it could not conclude that it affected other anthropometric measurements [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth outcomes of infants fed formula supplemented with these ingredients are worth evaluating. Some systematic reviews about comparisons between infants fed with standard formula and those fed with milk fat globule membrane-supplemented formulas, palm olein-containing formulas, prebiotic-supplemented formulas, or taurine-containing formulas revealed no differences in anthropometric measurements [ 50 , 51 , 52 , 53 ]. A meta-analysis by Wang et al indicated that nucleotide supplementation could increase the rate of weight gain; however, it could not conclude that it affected other anthropometric measurements [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity in the MFGM composition is probably a major reason for the discrepancy in the beneficial effects of MFGM supplementation in children (Ambrozej et al, 2021). The concentration of individual MFGM components still shows large variation, and underlying the molecular mechanisms of MFGM for infant health are still ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial variations in the types and amounts of PL, sialic acid, and membrane protein components are observed depending on the source and processing methods ( Brink et al, 2020 ; Qu et al, 2019 ). Heterogeneity in the MFGM composition is probably a major reason for the discrepancy in the beneficial effects of MFGM supplementation in children ( Ambrożej et al, 2021 ). The concentration of individual MFGM components still shows large variation, and underlying the molecular mechanisms of MFGM for infant health are still ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro , preclinical, and clinical studies have demonstrated numerous potential health benefits of MFGM ( 9 , 10 ). A systematic review and meta-analysis of MFGM supplementation in infants and children supported beneficial effects of MFGM on cognitive development and on reduction in otitis media incidence ( 29 ). Bolstered by these lines of evidence, bovine milk-derived MFGM preparations are available on a commercial scale from several sources and are added to some infant formulas currently on the market ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence for the MFGM to inhibit infections in clinical studies is less conclusive and varied from a reduced longitudinal prevalence of diarrhea ( 31 , 32 ) to no difference in diarrheal incidence between control and MFGM-containing experimental diets ( 33 , 34 ). Thus, the overall conclusion of the systematic review and meta-analysis was that the effect of MFGM formula supplementation on diarrheal diseases, including RV, was conflicting and weak ( 29 ). The inconsistent findings from human studies may be explained by differences in MFGM formulations used in the supplementation studies.…”
Section: Discussionmentioning
confidence: 99%